Pelanggaran Etika Pariwara dalam Iklan Affiliate Shopee di Thread X - Firda Nurmaulida; Pingkan Wulandari; Sofia Aziza Hasbudi; Fajar Junaedi (Universitas Muhammadiyah Klaten, 2025)
Affiliates are people who promote a company's goods or services. They can be bloggers, website owners, social media users, or other digital marketers. Affiliates use affiliate links to direct customers to the company's site and receive a commission on sales made through the affiliate links.The purpose of this research is to identify ethical violations in Shopee affiliate advertisements on thread X. The theories used are affiliate and advertising ethics. The research method used is descriptive qualitative. This study found that affiliate accounts on social media X violate advertising ethics for their own gain.